PELATIHAN MENGIDENTIFIKASI KECERDASAN MAJEMUK SISWA BAGI GURU-GURU BAHASA INGGRIS SMA KOTA JAYAPURA - Budi Rahayu; Yulini Rinantanti (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2021)
Abstract Improving the quality of education has always been done continuously by the government, the teachers, and other parties interested in education. However, the fact shows that there are still many challenges that we still need to overcome, one of them being teachers’ lack of understanding their students’ cognitive condition. This current program is one of the ways to solve the problem, that is training SMA English teachers in Jayapura to enable them to identify their students’ cognitive condition, especially their multiple intelligences. Different person may have different types of multiple intelligence. The type of the multiple intelligence one has will influence the way he or she think and see the world. Multiple intelligence consists of Linguistics, Mathematics, Music, Sapatial, Kinsthetic, Interpersonal, Intrapersonal, and Natural.. The training was conducted through a lecture session and practice. A pre-test and post-test were given before and after the training. The result of pre-test shows that English teachers of senior high schools in Jayapura are still not familiar with multiple intelligences. After training was conducted, most participants believe that multiple intelligence can be used for the basis in preparing teaching materials in order the students to absorb the materials well, resulting in the better mastery of English. Abstrak Meningkatkan kuaitas pendidikan telah terus dilakukan oleh peerintah, para guru, dan pihak-pihak lain yang terkait. Namun tetap saja fakta membuktikan bahwa masih banya hal yang perlu kita perbaiki, salah satunya adalah kurangnya pemahaman guru terhadap kondisi kognitif siswa. Program ini adalah salah satu upaya untuk mengatasi masalah ini, yaitu melatih para guru untuk dapat mengenali kondisi kognitif siswa, khususnya dalam hal kecerdasan majemuk. Setiap orang memiliki kecerdasan majemuk yang berbeda. Kecerdasan majemuk yang dimiliki seseorang akan berpengaruh terhadap cara berpikir seseorang. Kecerdasan majemuk terdiri dari kecerdaan Linguistik, Matematik, Musik, Spatial, Kinestetik, Interpersonal, Intrapersonal, dan Natural. Kegiatan ini dilakukan dengan cara ceramah, dan praktek. Pre test dan Post test diadakan sebelum dan sesudah sesi ceramah dan praktek. Hasil pre test menunjukkan bahwa para guru masih kurang faham dengan kecerdasan majemuk. Sementara hasil post test menunjukkan bahwa para guru yakin kecerdasan majemuk dapat dijadikan pedoman dalam membuat perencanaan pembelajaran agar siswa dapat menguasai materi pembelajaran Bahasa Inggris.